The Underexplored Species: Selective Participation in Direct Democratic Votes. Issue 1 (28th September 2015) - Sciarini, Pascal; Cappelletti, Fabio; Goldberg, Andreas C.; Lanz, Simon
Abstract: While electoral research usually distinguishes voters from abstainers, in the Swiss direct democratic context one needs to take into account a third category of citizens, the selective voters, who decide anew at each vote whether they will participate or not. This article offers an investigation of this common but under‐researched form of participation. To that end, we take advantage of a unique data‐set linking official turnout data with survey data. Our results show that selective voters constitute the bulk of the electorate. While they form a heterogeneous group in terms of socio‐demographic characteristics, selective voters lean more towards abstainers than towards permanent voters with respect to political variables. We argue that this is not necessarily bad news in terms of democratic theory.